Comparative study of seasonal incidence (Monsoon) of Chicken coccidia in different eight districts , Marathwada region (M.S.) - Nikam, S V; Kanse, V S; Jadhav, B N; Jaid, E L (Journal of Experimental Sciences, 2012)
During the period of 4 months (Monsoon Season) that is from, Jul,2011 - Oct, 2011, total 699 faecal samples were examined for coccidial infections, out of which 172 samples were positive the percentage of prevalence being 25.40%. Comparative study of different eight districts shows minor differences in prevalence.